2014
DOI: 10.1016/j.geomorph.2014.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Role of wave forcing, storms and NAO in outer bar dynamics on a high-energy, macro-tidal beach

Abstract: Outer sand bar dynamics on a high-energy macro-tidal beach were investigated using long-term (multi-year) field datasets of intertidal morphology and offshore bathymetry. Utilising a 15-year time-series of Argus video images, five distinct outer bar types were identified: Mega Rip, Longshore, Crescentic, Crescentic Attached and Welded. The most common classification was Crescentic Attached, with the outer bar oscillations being out of phase with the inner bar oscillations, as would be expected for the shore-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 66 publications
(83 reference statements)
2
69
0
3
Order By: Relevance
“…wave heights over 2.5 m and a minimum duration of 12 h; storm groups with calm periods of less than 24 h between them were considered a single storm-group event. The threshold above for significant wave height coincides with the 0.95 quantile defined by Masselink et al (2014) and with the minimum wave height threshold proposed by Ribera et al (2011).…”
Section: Wave Data and Storm Selectionsupporting
confidence: 83%
“…wave heights over 2.5 m and a minimum duration of 12 h; storm groups with calm periods of less than 24 h between them were considered a single storm-group event. The threshold above for significant wave height coincides with the 0.95 quantile defined by Masselink et al (2014) and with the minimum wave height threshold proposed by Ribera et al (2011).…”
Section: Wave Data and Storm Selectionsupporting
confidence: 83%
“…Consistent with this assumption, many studies have suggested that the North Atlantic Oscillation (NAO) may control the occurrence of storm events in the Atlantic, and thus potentially influence coastal morphological changes. The role of the NAO in coastal morphological dynamics has been suggested by Masselink et al [48] to explain medium-term outer sand bar dynamics in the southwest of England (Perranporth). It was also suggested by Thomas et al, after analyzing beach rotation at South Sands Tenby in West Wales [49,50] and O'Connor et al [51] concerning long-term shoreline and ebb channel evolution in northwest Ireland.…”
Section: Discussionmentioning
confidence: 91%
“…First, temporal trends of events were analysed by looking at both monthly and inter-annual changes. We compared the inter-annual changes of events with different atmospheric oscillations (NAO, EA, SCAND and WEPA), as done in previous wave climate studies on the west coast of Europe, e.g., [27,[32][33][34]. Second, the temporal clustering was evaluated by comparing the time between consecutive events.…”
Section: Methodsmentioning
confidence: 99%